Gerasim Zelić e il suo tempo - Steenwijk, Han; Fin, Monica (Biblioteca di Studi Slavistici, 2019)
Gerasim Zelic (1752-1828) is one of the most emblematic figures of the Serbian cultural scene between the 18th and 19th century. He as an archimandrite of the Serbian Orthodox monastery of Krupa, a diplomat and a writer. From 1794 to 1811, Zelic held the position of Vicar-General of the Serbs in Dalmatia and, as such, was one of the main actors of the events related to the confessional controversy that stirred the region at the time. His autobiography, entitled Žitije and published in Budapest in 1823, also places him among the protagonists of a crucial period for the birth of the new Serbian literature. Following a multidisciplinary approach, the essays collected in the volume Gerasim Zelic e il suo tempo analyse Gerasim Zelic's story, his involvement in the events related to the confessional controversy in Dalmatia and his literary activity, bringing the discussion to the era in which the Serbian archimandrite lived. Particular attention is paid to the context in which Zelic worked, namely the Balkan peninsula, as well as to the cultural history of the Serbs of Hungary between the 18th and 19th century.